2017
DOI: 10.1177/1369433217732498
|View full text |Cite
|
Sign up to set email alerts
|

Renovation of existing steel railway bridges: Field test and numerical simulation

Abstract: Renovation of the aged steel railway structures is of vital importance due to their long service life after completion. A strengthening method for aged steel railway bridges by using rubber-latex mortar, glass fiber-reinforced polymer plates, lightweight rapid hardening concrete, and reinforcing bars was introduced in this article. To confirm the real effect of the present strengthening method, field tests were performed on two aged steel railway bridges that have been in service for 87 and 61 years, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…22,23 Silionis et al 24 indicated that damage modes cause extensive stress redistribution on thinwalled structures. Lin et al 25 confirmed the stress reduction effects of railway bridges in real service conditions through stress variations on the mid-span section due to running trains in the field test. Fargier Gabaldo´n et al 26 revised the principles governing moment redistribution due to creep and developed a novel graphical aid suitable for hand calculations to estimate the magnitude of tensile stresses due to moment redistribution for the cantilever bridges.…”
Section: Introductionmentioning
confidence: 73%
“…22,23 Silionis et al 24 indicated that damage modes cause extensive stress redistribution on thinwalled structures. Lin et al 25 confirmed the stress reduction effects of railway bridges in real service conditions through stress variations on the mid-span section due to running trains in the field test. Fargier Gabaldo´n et al 26 revised the principles governing moment redistribution due to creep and developed a novel graphical aid suitable for hand calculations to estimate the magnitude of tensile stresses due to moment redistribution for the cantilever bridges.…”
Section: Introductionmentioning
confidence: 73%
“…[12][13][14] A concrete bridge deck also provides an excellent noise reduction strategy for real applications. For instance, Saito et al 15 and Lin et al 16 performed hammering tests on a scale model of an I-shaped steel beam after casting a concrete deck. Vibration of the steel beam web was reduced substantially when the top flange was excited, but not when the web was excited.…”
Section: Introductionmentioning
confidence: 99%